(untitled) (Herald of the National Children’s Medical Center, 2022)
Currently, congenital pathology of the heart and great vessels, which is the root cause of early disability and death of children, especially the first year of life, is becoming increasingly important. The article presents the results of a retrospective analysis of outpatient cards for 64 children born with congenital heart defects for the period 2019-2020. in the Khorezm region of the Republic of Uzbekistan. The most common heart defect in children is the ventricular septal defect. The highest frequency of congenital malformations was registered in Khozarasp (21.9%) and Yangiarik (18.8%) districts, the lowest in Yangibazar district (1.6%) of Khorezm region. Complicated obstetric history of mothers of children born with congenital heart defects, as well as acute viral diseases in the first trimester of pregnancy and laboratory confirmed carriage of high Ig G titers to such TORCH infections as herpes, toxoplasmosis and cytomegalovirus, probably influenced the formation of congenital heart defects in children.